Perubahan Fisiologis Tubuh Selama Imobilisasi Dalam Waktu Lama - Rohman, Ujang (Journal Sport Area, 2019)
The scientific review manuscript from the results of this literature review elaborates the changes that occur in the body as an impact of old immobilization. Immobilization is a condition in which a person experiences movement limitations as a result of interference in the body's organs. The limitation of this physical movement as a physiological change in the body results from a period of time immobilization. Physiological changes during immobilization in a long time cause disruption of adaptation in the musculoskeletal includes permanent disruption of mobilization that will affect muscle endurance and decrease muscle mass, atrophy and muscle stability. In the cardiovascular section includes orthostatic hypotension disorders and thrombus formation, whereas on the respiration section includes disturbances in the decrease in various of lung volumes as a result of weakening of the respiratory muscles so that it affects the respiratory motion. By understanding the physiological changes that occur as a result of immobilization in a long time, it is expected that this literature review can find out how the prevention process and further the handling process.